Embedded, Cyber-Physical, and IoT Systems : Essays Dedicated to Marilyn Wolf on the Occasion of Her 60th Birthday /: Essays Dedicated to Marilyn Wolf on the Occasion of Her 60th Birthday. (2020) - Unknown
No abstract available